Exploitation of beneficial alleles from maize (Zea mays L.) landraces to enhance performance of an elite variety in water stress environments - Meseka, S.K.; Menkir, A.; Obeng-Antwi, K. (Springer, 2015)
Yield losses of maize due to drought stress (DS) in environments with limited rains can reach 100 %. Introgression of favorable alleles from diverse landraces into adapted elite varieties will improve performance, hence reducing losses. The objective of this study was to assess the performance of BC populations under DS and multiple locations (ML) after introgression of alleles from diverse maize landraces into an elite variety. Twelve backcross (BC1F2) populations together with their recurrent parent (TZLCOMP4C1) and a commercial hybrid (Oba Super1) were evaluated under DS, well watered (WW) conditions during the dry season, and in seven ML trials in Nigeria. Significant differences were observed among genotypes for all traits except for ear aspect score under DS conditions. Grain yield and most agronomic traits measured were highly significant (p\0.001) underWWconditions and across ML trials. In DS, eight of the 12 BC1F2 populations had similar mean grain yield compared to their recurrent parent. Four of these populations produced 3–7 % more grains than the recurrent parent. Yield improvement was accompanied by reduced barrenness, days to flowering, plant height and ear placement, and good plant and ear aspect scores. The eight BC1F2 populations should be subjected to recurrent selection under controlled DS, while four other BC1F2 populations with low grain yields could be subjected to additional backcross to increase frequency of favorable alleles for improved performance in stress environments. The resulting improved populations can be invaluable source materials for developing drought tolerant varieties and parental lines of hybrids.